INDUSTRIALISASI DAN PERDAGANGAN INTERNASIONAL - Santosa, Agus Budi (Fokus Ekonomi, 2006)
The effect of the industrialization in some less developed countries is reflected by the increasing of industry output which grows considerably faster compared to the gross domestic product, so that the market segment of the industry rise up.  It carries the consequences to the change of trading structure of the resulted product. In the level of theory concept, there is difference view towards industrialization and trading according to neo-classic perspective, structuralism and radicalism. Of the trading influence towards the result of the industry, it can be seen from industry productivity, protection costs, trading orientation, and growth of total production factor.Keyword: Less developed country, industrialization, and trading.